Additional description of Oribella fujikawae Mahunka (Acari, Oribatida) collected from Iran, with a key to world Oribella species - Mansoureh Ahaniazad; Mohammad Bagheri; Mohammad Ali Akrami (Persian Journal of Acarology)
An additional description of Oribella fujikawae Mahunka, 1982 is provided based on specimens collected from the northwest of Iran. An identification key to the known species of the genus Oribella is given.